Asynchronous gate-diffusion-input (GDI) circuits. - Morgenshtein, A. (IEEE Transactions on VLSI systems)
Novel gate-diffusion input (GDI) circuits are applied to asynchronous design. A variety of GDI implementations are compared with typical CMOS asynchronous circuits. Dynamic GDI state holding elements are 2× smaller than CMOS C-elements, 30% faster, and consume 85% less power, but certain CMOS elements are preferred when static storage is called for. A GDI bundled controller outperforms CMOS on all accounts, having 1/3 the delay and requiring less than half the area while consuming the same power. A combination CMOS-GDI circuit provides the optimal solution for qDI combinational logic, saving 1/3 the power, half the area, and 10% in delay relative to a CMOS implementation. GDI circuits also provide some measure of enhanced hazard tolerance.